Work Attitude, Practices and Environment as Drivers of Teachers Performance - Kintanar, Gemma (JPAIR Institutional Research, 2020)
A range of studies exploring what made a teacher perform has looked mostly into details about salary compensation as extrinsic motivation to reflect performance and effectiveness. As such, several studies have been conducted regarding the work performance of teachers as a pivotal issue in education but considered different variables in dealing with what has caused its deterioration. Anchored on the Balance theory and support theory on social learning and self-efficacy, this study examines what best drives teaching performance. This study is focused on finding out the relationship between work attitude, practices, and environment as drivers of teachers’ performance. The descriptive correlational research design was used to describe the levels of independent variables to teachers’ performance. Furthermore, multiple regression was employed to test the predictive power of independent variables to its dependent variable. Findings revealed on the level of work attitude of elementary teachers and job satisfaction gained the highest mean and self-efficacy as the lowest mean. It can also be gleaned on the results on the level of practices that student’s orientation got the highest mean and enhanced activities as the lowest. On the level of environment, classroom, and school-level indicators obtained the same mean. On determining teachers’ performance, it revealed that the effectiveness of teachers got the highest mean. The result implies that the three independent variables show a high correlation at a 0.01 level of significance. Analyses also showed that among all of the correlated variables, the work environment significantly predicts the teaching performance of the respondents.